2013
DOI: 10.5336/medsci.2012-30433
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity Study of Shortened Level of Expressed Emotion Scale in Adolescents

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Bu çalışmanın amacı, algılanan duygu dışavurum düzeyini değerlendirmek için ergenlerde kullanılan "Kısaltılmış Duygu Dışavurumu Düzeyi Ölçeği"nin Türk toplumuna uygulanabilirliğinin araştırılması için güvenilirlik ve geçerliliğinin incelenmesidir. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Çalışma üç farklı sosyoekonomik düzeyden okullardaki ergenleri kapsayan 1010 öğrenci ile yapıl-mıştır. Araştırmaya katılan öğrencilerin %57,4'ü kız, %42,5'i erkek olup, ortalama yaş 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This was developed by Nelis et al ( 16 ) and was translated into Turkish by Vural et al ( 17 ) in 2013. S-LEES consists of 33 items measuring the EE of the person perceived to be most important in the participant’s life over the previous three months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was developed by Nelis et al ( 16 ) and was translated into Turkish by Vural et al ( 17 ) in 2013. S-LEES consists of 33 items measuring the EE of the person perceived to be most important in the participant’s life over the previous three months.…”
Section: Methodsmentioning
confidence: 99%
“…Nelis et al ( 16 ) reported Cronbach’s alpha coefficients, a measure of reliability, of 0.88, 0.82 and 0.70 for the S-LEES, irritability and intrusiveness subscales, respectively. When the reliability scale was evaluated by Vural et al ( 17 ), Cronbach’s alpha coefficient was found to be as high as 0.90. The forms were completed by the adolescents themselves.…”
Section: Methodsmentioning
confidence: 99%
“…The scale developed by Nelis et al (Nelis, Rae, & Liddell, 2011) was translated into Turkish by Vural, Sığırlı, Eray, Ercan, and Kılıç (2013). The SLEES consists of 33 items measuring the EE of the person perceived to be most important in the participant’s life over the previous 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…The scale developed by Nelis et al ( 20 ) was translated into Turkish by Vural et al ( 21 ) in 2013. SLEES consists of 33 items measuring the EE of the person perceived to be most important individual in the participant’s life over the previous 3 months.…”
Section: Methodsmentioning
confidence: 99%